National Road Crash Injuries – An Estimation and Comparison with Previous National Studies - Subhan, F.; Kanwal, H.; Sulaiman, M.; Naeem, M. M.; I. Shafiq, M. M.; Sajjad, U.; Ajwad, A.; Aqdas, A. (The Nucleus, 2017)
Every year, approximately 1.24 million fatalities and 20 to 50 million non-fatal injuries occur worldwide due to road traffic collisions. This poses a serious social and economic challenge to all countries around the world. Effective road safety measures can only be introduced if the extent of the problem is thoroughly explored. Pakistan faces a similar problem and in spite of a rapidly growing population and sharp increase in vehicle fleet size, no real efforts have been made to obtain estimates of the number of injuries resulting from road traffic crashes every year. This study presents an attempt at estimating annual road crash injuries for Pakistan using data provided by Reputed world Organizations, including WHO (World Health Organization), IRF (International Road Federation), WB (World Bank), using two different measures of relative road safety. Annual road crash injuries for Pakistan were estimated using annual crash injuries data from seventy-four countries having vital registration systems. Results of this study were compared with past national studies on road crash injuries estimation which showed vast discrepancies because of use of insufficient or highly under-reported data or the use of flawed methods by those studies.